2010
DOI: 10.1152/physrev.00036.2009
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Actin Cytoskeleton-Plasma Membrane Interplay by Phosphoinositides

Abstract: The plasma membrane and the underlying cortical actin cytoskeleton undergo continuous dynamic interplay that is responsible for many essential aspects of cell physiology. Polymerization of actin filaments against cellular membranes provides the force for a number of cellular processes such as migration, morphogenesis, and endocytosis. Plasma membrane phosphoinositides (especially phosphatidylinositol bis- and trisphosphates) play a central role in regulating the organization and dynamics of the actin cytoskele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
447
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 429 publications
(455 citation statements)
references
References 414 publications
(462 reference statements)
5
447
0
3
Order By: Relevance
“…(2) Cell adhesion molecules: N-cadherin has been reported to be asymmetrically distributed during early neuronal development, in one of the earliest events during the establishment of asymmetry [48,72]. (3) Phosphorylated derivatives of the phospholipid phosphatidylinositol or phosphoinositides: as membrane-localized signaling molecules which interact with the actin cytoskeleton [73,74], PIP3, a member of this family, has been shown to promote neuronal polarization [75,76] and the formation of axonal filopodia [77].…”
Section: Discussionmentioning
confidence: 99%
“…(2) Cell adhesion molecules: N-cadherin has been reported to be asymmetrically distributed during early neuronal development, in one of the earliest events during the establishment of asymmetry [48,72]. (3) Phosphorylated derivatives of the phospholipid phosphatidylinositol or phosphoinositides: as membrane-localized signaling molecules which interact with the actin cytoskeleton [73,74], PIP3, a member of this family, has been shown to promote neuronal polarization [75,76] and the formation of axonal filopodia [77].…”
Section: Discussionmentioning
confidence: 99%
“…This pathway was described as being responsible for stimulating protein kinase (PK) activation, including mitogen-activated kinase protein (MAPK), which has been previously reported as an attendee in the regulation of oocyte meiotic resumption, in which it may act directly or indirectly [9]. Recent studies have shown that MAPK is required in gonadotropininduced meiotic resumption [35,38,39,44]. Other studies have also established that MAPK as well as protein kinase A (PKA) interrupts the communication between the CCs and the oocyte, thus decreasing the cyclic adenosine Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4 Metabolic correlation between phosphatidylserine (PS) and phosphatidylethanolamine (PE), found in the non-pregnant group, and phosphatidylcholine (PC), found in the pregnant group. PSS1 PS synthase-1; PSS2 PS synthase-2; PSD phosphatidylserine decarboxylase; PEMT phosphatidylethanolamine N-methyltransferase; ET ethanolamine transferase; EK ethanolamine kinase; CPT phosphoethanolamine cytidylyltransferase; EPT ethanolamine phosphotransferase; CT ethanolamine transferase; CK choline kinase monophosphate (cAMP) level in the female gamete, which initiates its meiotic resumption [26,29,35]. Therefore, we propose that the high PI intensity in the NP group indicates that the degradation of DAG has been not occurring or that it has been occurring at low activity, due to the reduced efficiency of meiotic resumption in this group.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, this may induce segregation of PIP 2 in membranes. Given the importance of this lipid in actin dynamics (for review see [87]), ERM-induced PIP 2 clustering may reveal to be of high physiological importance.…”
Section: -Conclusionmentioning
confidence: 99%
“…In turn, this may induce segregation of PIP 2 in membranes. Given the importance of this lipid in actin dynamics (for review see [87]), ERM-induced PIP 2 clustering may reveal to be of high physiological importance.At this stage, it is clear that membrane binding triggers conformational changes in ERM. Does this conformational change permit ERM interaction with actin and what is the part of phosphorylation in this process?…”
mentioning
confidence: 99%